Use of Information and Communication Technologies in Natural Calamities by Residents in a Flood-Prone Community: A Case in Leyte, Philippines - Asio, Ma. Victoria Stephane G.; Cagasan, Editha G. (Annals of Tropical Research, 2014)
Residents in disaster-prone areas use information and communication technologies (ICTs) to cope with risks. This study was conducted in a flood-prone barangay of Palo, Leyte to determine the informants’ use of ICTs in natural calamities. Following the grounded theory approach, the 23 informants were chosen using snowball sampling and were interviewed using an in-depth interview guide. The theoretical model generated from the data showed that in this flood-prone community, residents are exposed to various information sources that they use in the different phases of the disaster for various reasons. Although informants’ reasons for accessing and using ICTs were not primarily related to their use in times of disasters, their good access to these technologies proved useful in times of calamities. ICTs have also proven as crucial means of communication especially in giving residents warnings of an incoming disaster and in surviving and recovering from the disaster. Results suggest the need to enhance ICT access among residents and officials in disaster-prone communities.